On the reorganization of Irish education departments and the appointment of a minister of education - Graves, Arnold F. (Statistical and Social Inquiry Society of Ireland, 1882)
The control of matters educational in Ireland is divided between the following nine boards:?the National Board, the Intermediate Board, the Endowed Schools' Board, Erasmus Smith's Schools' Board, the Incorporated Society, the Commissioners of Charitable Donations and Bequests, the Science and Art Department of the Committee of Council on Education, the University of Dublin, and the Royal University. These are all either government departments or else bodies possessed of large endowments and enjoying charters and other state privileges. Besides these, there are other important educational boards, but as they cannot any of them be considered public institutions, I shall not deal with them in this paper.
Read before the Society, 13 June 1882
Keywords: Education in Ireland; Minister of education; Government education policy; 314.15